ANALYSIS OF BUSINESS PROFITABILITY OF RAWA BANGUN POLEWALI MANDAR VILLAGE, BATETANGGA VILLAGE - Lismayanti A, Lismayanti A; Anwar, Anwar; Ilham Wardhana Haeruddin, Muhammad (RADJA PUBLIKA, 2022)
This study aims to find out and analyze the rentability of the Rawa Bangun business. The population is a balance sheet for 6 years (2016-2021). And the sample is a comprehensive financial position and profit and loss report on the Rawa Bangun Tourism Business. This type of research is descriptive quantitative, where the data used is equity and own capital. The data collection technique used in this study is documentation. Then the data analysis technique used is Rentability Analysis which consists of economic profitability (ROA) and profitability of own capital (ROE).The results show that the ability of tourism to make a profit using total assets from 2016-2021 is still below the industry standard of 30%. The reason for Tourism's ability to obtain profits using total assets is still below industry standards because of the low turnover of assets or in other words, the company has not been able to maximize the resources owned in the form of assets to generate attractiveness which will automatically increase profits. Meanwhile, the ability of tourism to make a profit using its own capital in 2016-2021 is above the industry standard of 40% even though in 2020-2021 it has decreased so that is said to be quite good, this is because tourism is able to manage its own capital in obtaining profits even though it is hampered by Covid.